Implementasi Sistem Pengendali On-Off Jarak Jauh PJU Berbasis IoT - Nasrullah Nasrullah; Jefri Lianda; Hikmatul Amri; Adam Adam; Khairudinsyah Khairudinsyah (KOLONI, 2026)
The advancement of Internet of Things (IoT) technology has enabled the development of smart systems for controlling and monitoringpublic infrastructure, including Public Street Lighting (PSL). This study presents the implementation of an IoT-based remote on-off control systemdesigned to improve the efficiency and flexibility of street lighting management. The proposed system employs an ESP32 NodeMCUmicrocontroller as the control unit, a relay module to switch the lighting load, and the Blynk application to provide a user-friendly interface for remote operation and monitoring through a smartphone. The research was carried out through hardware and software design, systemintegration, and functional performance testing. Experimental results demonstrated that the developed system responded successfully toall ON and OFF commands transmitted over the internet, achieving a 100% success rate under stable network conditions. In addition,users were able to monitor the operational status of the street lights in real-time, allowing faster and more efficient management from remote locations. The implementation results indicate that the proposed IoT-based control system provides a practical, reliable, and cost-effective solution for modern public street lighting management while supporting the realization of smart city infrastructure.